A finer-grained linguistic profile of Alzheimer's disease and Mild Cognitive Impairment - Chapin, Kayla; Clarke, Natasha; Garrard, Peter; Hinzen, Wolfram (Journal of neurolinguistics, 2022)
Linguistic measures in spontaneous speech have shown promise in the early detection of Alzheimer's disease (AD), but it remains unknown which specific linguistic variables show sensitivity and how language decline relates to primary memory deficits. We hypothesized that a set of fine-grained linguistic variables relating specifically to forms of syntactic complexity involved in referencing objects and events as part of episodes would show sensitivity. We tested this in speech samples obtained from a picture description task, maximally isolating language deficits from the confound of episodic memory (EM) demands. 105 participants were split into Mild Cognitive Impairment (MCI), Mild-to-Moderate AD, and healthy controls (HC). Results showed that groups did not differ on generic linguistic variables such as number or length of utterances. However, AD relative to HC produced fewer embedded adjunct clauses, indefinite noun phrases, and Aspect marking, with moderate-to-large effect sizes. MCI compared to HC produced fewer adjunct clauses as well as fewer adverbial adjuncts. Together, these results confirm language impairment in AD and MCI at the level of specific linguistic variables relating to structures required for endowing narrative with specificity and episodic richness, independently of EM demands. •We measured language changes in spontaneous connected speech in MCI and AD.•Hypothesis-driven variables revealed group differences relative to controls.•Linguistic changes were related to specificity in referencing objects and events.•Spontaneous speech reveals and allows the tracking of cognitive decline.